Analysis of Factors Associated with Contact Dermatitis in Nickel Ore Processing Industry Workers in Morosi District - Ramadhany, Nanda Clara; Jayadipraja, Erwin Azizi; Rahmawati, Rahmawati (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: Dermatitis is one of the skin diseases that industrial workers tend to experience. The prevalence of dermatitis in 2021 is 19.5%, then in 2022 it is 21.7% and in 2023 it is 23.1%. The aim of this study was to analyze factors associated with contact dermatitis in nickel ore processing industry workers in Morosi District. Method: Type of quantitative research with Cross Sectional Study design. The sampel is 71 people Nickel Ore Processing Industry Workers in the smelting sector who live in Morosi District taken using a simple random sampling technique with the Chi-square test and close relationship test. Results:the chi-square test found p values for age (0.000) and φ (0.505), p values for length of contact (0.000) and φ (0.507), p values for frequency of contact (0.001) and φ (0.399), personal protective equipment (0.023 ) and φ (0.270), personal hygiene (0.000) and φ (0.827). Conclusion: The conclusion of this study is that there is a moderate relationship between age and length of contact with contact dermatitis. There is a weak relationship between the frequency of contact and use of personal protective equipment with contact dermatitis and there is a strong relationship between personal hygiene and contact dermatitis in nickel ore processing industry workers in Morosi District